(untitled) - Griffiths, David J. (New Jersey, 1995)
The author avoids the temptation to include every possible relevant topic, instead presenting students with material that they can easily focus on in a complete treatment with few distractions and diversions. Fundamental principles are covered, quantum theory is presented, and special techniques are developed for attacking realistic problems. The innovative two-part coverage is entertaining and informative, organizing topics under basic theory and assembling an arsenal of approximation schemes with illustrative applications linked closely to the text.
Cơ học lượng tử
Keywords: Mechanics,Quantum theory